Environmental impacts of certification programmes at Colombian coffee plantations - Diego Ivan Caviedes Rubio; Daniel Ricardo Delgado; Alfredo Olaya Amaya (Economía Agraria y Recursos Naturales)
Certification programmes are often promoted as a sustainable solution for the negative environmental and socio-economic effects generated by agricultural activities. This scope review assesses the seven most adopted certification programmes in Colombian coffee plantations and their ecological, economic and social impacts. In addition, this scope review characterises the coffee regions where the studies are conducted and the main methodological approaches that are used. The review revealed that the main methodological approach used in the studies is the mixed approach and that the largest number of studies is not conducted in the departments that report the highest coffee production rates. The main certification program assessed in this review is the Rainforest Alliance. However, this study also reports the existence of several gaps caused by multi-certification effects. In total, 87 reports of ecological, economic, and social impacts were identified. Out of the 87 environmental impact reports of the certifications identified in this study, 66 were positive and only 21 were negative.